HOW UNIVERSITIES COMMUNICATE WITH THE PUBLIC VIA SOCIAL MEDIA: A CONTENT ANALYSIS - Eger, Ludvík; Gangur, Mikuláš (Communication Today, 2024)
In recent years, social media have developed the strong potential to effectively communicate and to create a value proposition about university educational services, research activities and their third role. The social media content should be designed in a way which creates value for social media users to build a stronger level of engagement and facilitate brand communication. The conducted research not only investigates how selected universities use their profiles on Facebook and Instagram and communicate with the public, but the analysis also focuses on a deeper understanding of the characteristics that influence the interactivity and the relationship between a selected university and its page visitors. The findings reveal that different types of post sources generate different engagement per post (by follower) and behaviour of target groups. Furthermore, content analysis was performed to assess differences among universities in their communication. The findings document how selected categories according to uses and gratifications theory influence target groups’ engagement. The results offer scholars and practitioners new knowledge for communication in the higher education field using social media.